On‐treatment changes of serum Wisteria floribunda agglutinin‐positive Mac‐2 binding protein are associated with the regression of liver fibrosis in chronic hepatitis B patients on interferon α add‐on therapy. Issue 8 (16th April 2019) - Liu, Tianhui; Sun, Yameng; Zhou, Jialing; Yang, Fang; Zou, Xia; Wang, Lin; Wu, Xiaoning; Chen, Yongpeng; Piao, Hongxin; Lu, Lungen; Jiang, Wei; Xu, Youqing; et al.
Abstract: Wisteria floribunda agglutinin‐positive Mac‐2‐binding protein (M2BP) has been identified as a predictor for the response of interferon α (IFN‐α) in patients with viral hepatitis. However, whether serum glycosylation isomer of M2BP (M2BPGi) was associated with the regression of liver fibrosis in patients with chronic hepatitis B (CHB) during IFN‐α add‐on therapy is still unknown. CHB patients were treated with entecavir for 26 weeks followed by entecavir plus pegylated IFN‐α for 52 weeks. Liver biopsies were taken at baseline and treatment week 78. The regression of fibrosis was identified according to Ishak standard or Ishak plus Progressive‐Indeterminate‐Regressive (P‐I‐R) standard. Serum M2BPGi and liver function tests were measured at baseline and every 26 weeks of treatment. A total of 72 CHB patients were included in the present study. Serum M2BPGi was correlated with fibrosis and necroinflammation both at baseline and week 78. If Ishak standard was used as the reference, only the percent change of M2BPGi at week 52 from week 26 (Δ%M2BPGi26w‐52W ) was independently associated with fibrosis regression at treatment week 78, the area under the ROC curve (AUROC) of Δ%M2BPGi26w‐52W for predicting fibrosis regression was 0.705. As for Ishak plus P‐I‐R standard, the AUROC of the predictive model for fibrosis regression (0.896*M2BPGi52W + 0.363*necroinflammation score0w + 2.051*Ishak score0w – 4.489) was 0.888. These data indicated that dynamic changes of serum M2BPGi were associated with fibrosis regression in CHB patients on IFN‐α add‐on therapy. Highlight: Serum M2BPGi was correlated with fibrosis and necroinflammation. Dynamic changes of serum M2BPGi were associated with fibrosis regression in CHB patients on IFN α add‐on therapy.